Nonalcoholic Fatty Liver Disease and the Risk of Atrial Fibrillation - Abou Omar, Mahmoud A.; Alaarag, Ahmed; Abd-Elsalam, Sherief; El-Abgeegy, Mohamed; Ahmed, Rehab; Mohamed, Ahmed Abdelhaleem; Khalil, Mahmoud; Abo-Amer, Yousry Esam-Eldin; Elkadeem, Mahmoud; Yousef, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is now the factor behind the development of liver cirrhosis, liver cell failure, and liver transplantation in many cases. However, its relation to atrial fibrillation (AF) could not be cleared up. AIM: The purpose of the study was to evaluate prevalence of AF in the setting of NAFLD; the association between them, and to evaluate risk factors of AF in this category of patients. METHODS: This cross-sectional study was performed on 400 patients between January 2018 and June 2019. These patients were analyzed for the presence of NAFLD and presence of persistent or chronic AF. RESULTS: There were 138 patients with NAFLD, and 20 patients with persistent or permanent AF. Factors associated with AF were old age, male gender, and high values of aspartate aminotransferase, alanine-aminotransferase, γ-glutamyltranspeptidase, and serum uric acid. The participants with AF had a significantly greater prevalence of NAFLD than those without AF. CONCLUSION: Incidence and prevalence of atrial fibrillation in NAFLD patients were high. Severity of liver disease was an important predictor of new-onset atrial fibrillation.